U.S. Audit Partner Rotations - Laurion, Henry; Lawrence, Alastair; Ryans, James P. (The Accounting Review, 2017)
ABSTRACT We investigate the effects of audit partner rotation among U.S. publicly listed firms, utilizing the fact that audit partners are periodically copied by name in public correspondence between issuers and the Securities and Exchange Commission. Relative to non-rotation firms, we find no evidence of a change in the frequency of misstatements following the partner rotation; however, there is an increase in the frequency of restatement discoveries and announcements. We also find an increase in deferred tax valuation allowances. Overall, the results provide some evidence suggesting that U.S. partner rotations support a fresh look at the audit engagement. JEL Classifications: M41; M42; M48. Data Availability: Data are publicly available from sources identified in the article.